2012
DOI: 10.1038/tp.2012.58
|View full text |Cite|
|
Sign up to set email alerts
|

Environmental enrichment rescues female-specific hyperactivity of the hypothalamic-pituitary-adrenal axis in a model of Huntington's disease

Abstract: Huntington's disease (HD) has long been regarded as a disease of the central nervous system, partly due to typical disease symptoms that include loss of motor control, cognitive deficits and neuropsychiatric disturbances. However, the huntingtin gene is ubiquitously expressed throughout the body. We had previously reported a female-specific depression-related behavioural phenotype in the R6/1 transgenic mouse model of HD. One hypothesis suggests that pathology of the hypothalamic-pituitary-adrenal (HPA) axis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 46 publications
4
56
2
Order By: Relevance
“…One body of research has identified depression to be associated with altered hypothalamic-pituitary-19 adrenal (HPA)-axis functioning (44)(45)(46)(47), and these mechanisms have been proposed for sex differences in depressive behaviours in rodents [48]. As yet, sex differences in HPA-axis functioning in human HD carriers have not been explored and this would be an interesting area for future research as sex differences in response to stress have been found to alter depending on the type of stressor and duration of exposure [48]; and a multitude of chemical, environmental and psychological stressors may affect individuals with HD.…”
Section: Discussionmentioning
confidence: 99%
“…One body of research has identified depression to be associated with altered hypothalamic-pituitary-19 adrenal (HPA)-axis functioning (44)(45)(46)(47), and these mechanisms have been proposed for sex differences in depressive behaviours in rodents [48]. As yet, sex differences in HPA-axis functioning in human HD carriers have not been explored and this would be an interesting area for future research as sex differences in response to stress have been found to alter depending on the type of stressor and duration of exposure [48]; and a multitude of chemical, environmental and psychological stressors may affect individuals with HD.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory and others have previously demonstrated that environmental enrichment can rescue the affective phenotypes and the abnormal physiological stress response in several disease models (Du et al, 2012;Li et al, 2014;Pang et al, 2013). However, there is growing evidence that the potential benefits of environmental enrichment extend beyond the exposed animal.…”
Section: Paternal Environmental Enrichment Had No Influence On F1 Offmentioning
confidence: 99%
“…EE rescues the depression-like phenotype and corrects HPA-axis dysregulation in a mouse model of alcohol withdrawal . EE also has the capacity to influence peripheral stress-response as demonstrated by its correction of adrenal hyper-responsivity pathology in a mouse model of Huntington's disease (Du et al, 2012). In normal rodents, EE has consistently been shown to reduce anxiety-like behavior in the elevated-plus maze and the open-field test (Sztainberg et al, 2010), with recent evidence suggesting the requirement of a minimum 3-week enrichment period (Leger et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Upregulation or over-expression of BDNF can rescue some symptoms of Huntington's disease in animal models 71,[111][112][113] . Consistent with the expression patterns noted above, BDNF is associated with memory and learning 108,114 and with body weight and energy homeostastis at both central 115 and peripheral 116, 117 levels.…”
Section: D-kefs Trail Makingmentioning
confidence: 99%
“…The paradigm of environmental enrichment employs increased mental, physical and social stimulation in animal models to enhance neurological input, thereby modulating brain activity and physical parameters to impact on disease progression [62][63][64][65][66][67] . A number of studies have shown the benefits of such an approach in Huntington's disease transgenic animal models, with evidence for it being able to delay the onset of motor abnormalities, slow disease progression, reduce impairments to weight loss, balance and physiological factors, and increase both neurogenesis and CNS levels of neurotransmitter receptors, neurotrophins and factors related to synaptic signal transduction pathways [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82] .…”
Section: List Of Figuresmentioning
confidence: 99%